Pomegranate peels and seeds as a source of phenolic compounds: effect of cultivar, by-product, and extraction solvent - Campos, Lara (2022)
The nutraceutical properties of Punica granatum L. are not restricted to the edible portion of the fruit but also to the peels and seeds, flowers, leaves, and tree bark. The recovery and valorization of the peel and seeds (ca. 50% of the whole fruit), besides the positive environmental impact, can be viewed as a source of natural bioactive compounds. Thus, the bioactive properties of extracts of pomegranate peel and seeds from Acco and Wonderful known cultivars, as well as of the novel Big Full cultivar, were evaluated. The dried and ground pomegranate by-products were submitted to a conventional solid/liquid extraction with ethanol/water mixtures (0%, 25%, 50%, and 75% of EtOH, v/v). The obtained extracts were characterized in terms of total phenolic compounds (TPC), total flavonoids (TF), and antioxidant activity (AA), determined by the DPPH radical scavenging activity and expressed as IC50 (half maximum inhibitory concentration). With the exception of the Acco cultivar, the extraction yield (EY) was higher for peels, whose extracts showed higher TPC, TF, and IC50 (lower AA). The extracts obtained from the by-products of the Big Full cultivar had a statistically higher overall bioactive potential (TPC: 0.36 mg GAE/mg extract; TF: 0.031 mg CATE/mg extract; IC50: 0.51 mg/mL) compared to the other two studied cultivars. Furthermore, the EY was enhanced by solvents richer in ethanol (50-75%), allowing obtaining extracts richer in TPC and TF with higher AA. Finally, it was shown that EY combined with bioactive data allowed a satisfactory principal component unsupervised differentiation of the pomegranate extracts according to the type of by-product used.